2012
DOI: 10.1007/s00265-012-1370-z
|View full text |Cite
|
Sign up to set email alerts
|

Untested assumptions about within-species sample size and missing data in interspecific studies

Abstract: Phylogenetic comparative studies rely on speciesspecific data that often contain missing values and/or differ in sample size among species. These phenomena may violate statistical assumptions about the non-random variance component in sampling effort. A major reason why this assumption is often not fulfilled is because the probability of being sampled (i.e., being captured or observed) may depend on species-specific characteristics. Here, we test this assumption by using information on within-species sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
4
13
0
Order By: Relevance
“…These results support the notion that while large ranges are bound to overlap with more sampling locations (compare Garamszegi & Møller, 2012), large, irregularly shaped ranges are severely constrained in the detail with which a given number of records could cover them. Range size was the single most important predictor, with a strong positive effect on record count and a strong negative effect on range coverage.…”
Section: Range Geometrymentioning
confidence: 99%
“…These results support the notion that while large ranges are bound to overlap with more sampling locations (compare Garamszegi & Møller, 2012), large, irregularly shaped ranges are severely constrained in the detail with which a given number of records could cover them. Range size was the single most important predictor, with a strong positive effect on record count and a strong negative effect on range coverage.…”
Section: Range Geometrymentioning
confidence: 99%
“…An index of specialization is only as reliable as the underlying data. The quality of information about traits varies from species to species, might be incomplete or inaccurate in some cases, depending on the quality and number of studies conducted on each species (Ducatez & Lefebvre, ; Garamszegi & Møller, ; McKenzie & Robertson, ). Furthermore, the type of variable used to fill out the trait‐features can also influence the index.…”
Section: Discussionmentioning
confidence: 99%
“…Most statistical analyses assume that single observations provide equally precise information about the deterministic part of total process variation; that is, the standard deviation of the error term is constant over all values of the predictor variable (Sokal & Rohlf, ). Garamszegi & Møller (, , ) have shown that bias due to variation in sample size among observations is a major problem in comparative analyses and equally significant as the biases caused by treating species‐specific estimates as statistically independent. If this assumption of similarity in sampling effort is violated, weighting each observation by sampling effort allows the use of all data, giving each datum a weight that reflects its degree of precision due to sampling effort (Draper & Smith, ; Sokal & Rohlf, ).…”
Section: Methodsmentioning
confidence: 99%
“…If this assumption of similarity in sampling effort is violated, weighting each observation by sampling effort allows the use of all data, giving each datum a weight that reflects its degree of precision due to sampling effort (Draper & Smith, ; Sokal & Rohlf, ). This procedure also allows both rare and common species to be included and hence avoids any bias in sampling due to rarity (Garamszegi & Møller, ). Therefore, we weighted statistical models by sample size.…”
Section: Methodsmentioning
confidence: 99%